KESENJANGAN PENDAPATAN LAKI-LAKI DAN PEREMPUAN DI KABUPATEN SRAGEN TAHUN 2018 - Middia Martanti Dewi (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
Government efforts to eliminate gender inequality have not yet yielded sweet results. The large number of female professional staff in Sragen Regency apparently was not followed by the high contribution of women's income. Professionals who should have high incomes have not been able to contribute high incomes. This condition may be due to the income gap between men and women. The writing of this study aims to see whether there are still income gaps between men and women. As well as seeing differences in employment characteristics between men and women found in Sragen Regency. This study was written using data from August 2018 Sakernas in Sragen Regency which was analyzed descriptively using graphical visualization. It turns out that there are still visible income gaps between men and women both with the status of entrepreneurs and workers. Besides income, the difference between men and women is also seen in the length of working hours, education level and employment status. Men have longer working hours with more vocational secondary education and more entrepreneurship status. Whereas women work shorter hours with more low education levels and more family/unpaid employee status.